HR Tech and Employee Experience: Exploring the Role of AI, Automation, and People Analytics in Modern Workplaces - Zunaira Mahmood; Sarfaraz Raza Khan; Dr. Shahid Ali Durrani; Muhammad Zulqarnain; Dr. Osama Ali (Indus Journal of Social Sciences, 2025)
The research investigates HR technology effects on corporate experience alongside workforce output and work commitment with practical implementation obstacles and strategies. The main research goal focused on studying how artificial intelligence and automation together with people analytics improve human resource capabilities and increase employee connection and enhance work productivity. Organizations encounter essential difficulties during their implementation of these technological solutions according to the research findings. Twenty-five percent of HR professionals and employees from different businesses participated in this study through structured surveys under a quantitative framework. Random sampling methodology produced beneficial inquiry representation because it integrated various subject categories. The researchers applied descriptive statistics alongside regression models for interpretation of study results. Research shows that AI recruitment deployment exists in 75% of organizations together with payroll automation in 85% of organizations. AI tools in HR platforms deliver better relationships between employees and the workplace in addition to improved learning experience and better performance management. The research documented several significant obstacles which include both AI bias problems in addition to privacy issues and employee reluctance. People analytics grew into an essential prediction-based tool which organizations used to enhance their employee retention efforts. Research needs to investigate how AI influences the HR culture in the future along with ethical matters and employee welfare concerns. Ordinary AI and methods to reduce bias require development to establish responsible AI implementation within HR operations. Workforce management experiences innovation through HR technology while organization success depends on strategic ethical considerations. The relationship between modern organizational systems depends on an accurate mix of technological solutions and employee-guided strategies to reach the best outcomes for staff satisfaction and operational excellence.